DARI KONGRES KE REGULASI: PERAN ORGANISASI PEREMPUAN PADA LAHIRNYA UNDANG-UNDANG PERKAWINAN 1974 - Ipong Jazimah; Van Kim Hoang Ha; Arifin Suryo Nugroho; Nungki Marlia Ujiyani (Universitas Muhammadiyah Palembang, 2026)
The enactment of the Marriage Law of 1974 was the result of a long and complex process marked by persistent struggles and dynamic developments. Behind this achievement, women's organizations played a significant role. Before its enactment, existing marriage regulations, whether based on religious law or customary law, were considered inadequate in providing legal protection for women. Consequently, there emerged a strong demand for a specific marriage law that would better safeguard women's rights within marriage. This study aims to examine the role of women's organizations in the formulation and enactment of the Marriage Law, from the emergence of the initial idea to its official ratification in 1974. The study employs the historical research method, which consists of five stages: topic selection, heuristics (source collection), source criticism, interpretation, and historiography (historical writing). The findings reveal that the idea of establishing a Marriage Law first emerged during the First Indonesian Women's Congress. Women's organizations affiliated with the Indonesian Women's Association (PPII) actively supported and advocated for the enactment of the Marriage Law through various institutions they established, including the Marriage Consultation Bureau, KPKPAI (Komite Perlindungan Kaum Perempuan dan Anak-Anak Indonesia), BPPIP (Badan Perlindungan Perempuan Indonesia dalam Perkawinan), BP4 (Badan Penasihatan Perkawinan, Perselisihan, dan Perceraian), NTR Committee (Nikah Talak Rujuk), and ultimately the LPHN (Lembaga Pembinaan Hukum Nasional), which was responsible for drafting a nationally applicable Marriage Bill.